Aluminum alloy and preparation method and application thereof

By optimizing the element content and ratio in the Al-Mg-Si alloy and combining with the hot extrusion process, the problems of poor welding performance, heat resistance and crush performance of Al-Mg-Si alloys in the prior art are solved, and high strength, heat resistance and weldability are achieved.

CN119776704APending Publication Date: 2025-04-08CYMA PRECISION ALUMINUM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964399.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When preparing thin-wall multicellular structural profiles, existing high-strength Al-Mg-Si alloys cannot meet the requirements of welding performance, heat resistance and crush performance, and cracking is prone to occur during welding.

Method used

By optimizing the content and proportion of Mg, Si, Cu, Mn, V, Sc and Ni elements in Al-Mg-Si alloys, combined with the hot extrusion process in industrial production, a high-strength heat-resistant and collision-resistant weldable aluminum alloy with a strength of more than 340MPa was prepared.

Benefits of technology

The high strength, good heat resistance, impact resistance and welding properties of aluminum alloy are achieved, and the comprehensive performance requirements of thin-walled multi-cell structural profiles are met, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217988720000111
    Figure BDA0005217988720000111
  • Figure BDA0005217988720000121
    Figure BDA0005217988720000121
  • Figure BDA0005217988720000131
    Figure BDA0005217988720000131
Patent Text Reader

Abstract

The present invention discloses an aluminum alloy and a preparation method and application thereof, characterized in that, in terms of weight percentage, the aluminum alloy comprises the following components: Mg: 0.9-1.5, Si: 0.9-1.5, Fe: 0.12-0.60, Cu: 0.1-0.30, Mn: 0.2-0.6, V: 0.04-0.12, Sc: 0.04-0.12 and Ni: 0.05-0.15; the sum of the weight percentages of Mg and Si is 2.0-3.0; and the weight ratio of Mg to Si is 1.0-1.20. The present invention prepares a thin-walled multicellular structure profile having a strength of more than 340 MPa and good heat resistance, impact resistance and weldability through formula optimization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum alloy and a preparation method and application thereof. Background Art

[0002] Thin-walled polyhedral structures have excellent energy absorption characteristics and light weight, and can be widely used in anti-collision energy absorption devices for vehicles such as automobiles and airplanes. Al-Mg-Si aluminum alloys and hot extrusion forming processes are widely used to prepare thin-walled polyhedral structural products because of their good processing formability, scalable production, and low cost. The thin-walled polyhedral structural profiles prepared by hot extrusion are connected to other parts through welding processes. In order to ensure the energy absorption capacity of the anti-collision components, the welding strength of the thin-walled polyhedral structural materials should not be less than 70% of the parent material strength. In order to ensure the safety and reliability of the anti-collision energy absorption device during its life cycle, the thin-walled polyhedral structural materials also need to have excellent heat resistance and crash resistance. Among them, heat resistance is intended to evaluate the strength of the prepared thin-walled polyhedral structural materials against the attenuation of ambient temperature during the life cycle. At present, it is generally required that the yield strength attenuation of the material after being kept at 150°C for 1000h is less than 5%; while crash resistance is intended to evaluate the energy absorption capacity of thin-walled polyhedral structural materials during collision. The quasi-static crushing test method is currently generally used for evaluation. At present, the strength of extruded thin-walled multi-cellular Al-Mg-Si alloys is generally about 300 MPa. In order to further achieve lightweight transportation and improve fuel economy and environmental performance, it is extremely important to develop Al-Mg-Si alloys with higher strength, heat resistance, impact resistance and weldability.

[0003] There are many problems in the hot extrusion of thin-walled multicellular structures using existing high-strength Al-Mg-Si alloys. Thin-walled multicellular profiles can be prepared using AA6061 and AA6082 alloys with higher alloying element contents, but the strength of the alloy is lower than 340MPa, and the welding performance, heat resistance and crushing performance cannot meet the requirements; thin-walled multicellular structures cannot be prepared by hot extrusion using AA6110 and AA6013 alloys with high alloying element contents, and such alloys are prone to cracking during welding. It can be seen that the current high-strength Al-Mg-Si alloys cannot effectively prepare thin-walled multicellular profiles with excellent comprehensive properties. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention prepares a thin-walled multi-cellular structure profile with a strength exceeding 340MPa and good heat resistance, impact resistance and weldability through formula optimization.

[0005] The invention also provides a method for preparing the aluminum alloy.

[0006] The present invention also provides an aluminum profile, the raw material for preparing the aluminum profile includes the above-mentioned aluminum alloy.

[0007] According to one aspect of the present invention, an aluminum alloy is provided, comprising the following components, by weight percentage: Mg: 0.9-1.5, Si: 0.9-1.5, Fe: 0.12-0.60, Cu: 0.1-0.30, Mn: 0.2-0.6, V: 0.04-0.12, Sc: 0.04-0.12 and Ni: 0.05-0.15;

[0008] The sum of the weight percentages of Mg and Si is 2.0-3.0;

[0009] The weight ratio of Mg to Si is 1.0-1.20.

[0010] According to the first aspect of the present invention, there are at least the following beneficial effects:

[0011] The high-strength, heat-resistant, impact-resistant, weldable Al-Mg-Si alloy and its extrusion production method of the present invention studies the influence of elements such as Mg, Si, Mn, Cu, V, Sc and Ni on the structure and performance of Al-Mg-Si alloy, and combines the production process of Al-Mg-Si alloy extrusion in industrial production to provide a high-strength, heat-resistant, impact-resistant, weldable Al-Mg-Si alloy. Al-Mg-Si alloys with high Cu content have poor welding performance and extrusion forming performance; Al-Mg-Si alloys with low Mg / Si ratio have poor thermal stability and crushing performance; and Al-Mg-Si alloys with high Mg / Si ratio have lower strength and poor extrusion forming performance.

[0012] The present invention optimizes the contents of Mg, Si, Cu, Mn, V, Sc and Ni elements, the weight ratio of Mg / Si and the weight ratio of Mn / Fe in high-strength Al-Mg-Si alloys, and explores the regulating mechanism of the content and ratio of alloy elements on the mechanical properties, welding properties, thermal stability and crushing properties of Al-Mg-Si alloys, including the following two aspects:

[0013] In terms of alloy composition:

[0014] In the present invention, the content of Mg and Si elements are set in the range of 0.90-1.50wt.%, the total mass of Mg and Si elements is set in the range of 2.0-3.0wt.%, the mass ratio of Mg / Si is set in the range of 1.0-1.20, and the content of Cu element is set in the range of 0.10-0.30wt.%, which is the key point of the present invention; Mg and Si are the main alloying elements in Al-Mg-Si alloys, which are dissolved in the aluminum matrix during homogenization heat treatment and hot extrusion, and precipitate β' and β" phases during the subsequent aging heat treatment, causing aging Strengthening effect, the remaining Mg and Si are dissolved in the aluminum matrix to cause solid solution strengthening effect. In order to ensure that the strength of Al-Mg-Si alloy is greater than 340MPa, the total content of Mg and Si elements in the alloy is set in the range of 2.0-3.0wt.%. Si dissolved in the aluminum matrix can cause the following changes in the structure of Al-Mg-Si alloy: on the one hand, it can promote the coarsening of the precipitate phase during heat treatment and reduce the heat resistance of the alloy; on the other hand, it is easy to segregate at the grain boundary during quenching and aging heat treatment, reducing the grain boundary bonding strength and causing the alloy to collapse. Performance is reduced. Therefore, at the same total content of Mg and Si, the Mg / Si ratio in the alloy is increased, and the heat resistance and crushing performance of the Al-Mg-Si alloy are improved. It is generally believed that Mg atoms dissolved in the aluminum matrix can cause the distance between aluminum atoms to increase, while Si atoms are the opposite. Therefore, at the same total content of Mg and Si, the Mg / Si ratio in the alloy is increased, the vacancy diffusion activation energy and Zener-Hollomon parameter Z value of the Al-Mg-Si alloy are increased, and the corresponding hot extrusion deformation resistance is increased and the extrudability is reduced. The present invention improves the Mg / Si ratio in the alloy. The Si weight ratio is limited to 1.0-1.20, which is based on the preference of making the alloy have good heat resistance, crash resistance and extrudability at the same time. The Q phase (AlMgSiCu) formed by the combination of Cu element, Mg and Si can produce a greater strengthening effect, and the precipitated phase also has good thermal stability. However, the Cu element is easily segregated at the grain boundary, which increases the welding crack tendency of the Al-Mg-Si alloy. Based on making the alloy have high strength, heat resistance and weldability at the same time, the present invention limits the range of the Cu element to 0.10-0.30wt.%.

[0015] In some embodiments of the present invention, when the sum of the weight percentages of Mg and Si is 2.0-2.4, the aluminum alloy includes the following components: Cu: 0.20-0.30, V+Sc: 0.08-0.12, Mn: 0.40-0.6, Fe: 0.24-0.60 and Ni: 0.10-0.15.

[0016] In some embodiments of the present invention, when the sum of the weight percentages of Mg and Si is 2.4-3.0, the aluminum alloy includes the following components: Cu: 0.10-0.20, V+Sc: 0.12-0.16, Mn: 0.2-0.3, Fe: 0.12-0.30 and Ni: 0.05-0.10.

[0017] In the present invention, different contents of Cu, V and Sc elements are designed according to different contents of Mg and Si elements, which is the key point of the present invention. In the smelting of Al-Mg-Si alloy, V and Sc elements combine with Al element to form nano-scale Al (V, Sc) particles, which, on the one hand, cause dispersion strengthening effect; on the other hand, can refine grains during hot extrusion and subsequent welding, causing fine grain strengthening effect. However, excessive addition of V and Sc elements will have two adverse effects: on the one hand, it is easy to combine with Al, Fe, Mn elements to form coarse intermetallic compounds during the smelting process, so that the strength and toughness of the alloy are reduced; on the other hand, the hot extrusion deformation resistance is increased during the hot extrusion process, so that the extrudability of the alloy is reduced. Based on the purpose of making the alloy have high strength, heat resistance, extrudability and weldability at the same time, the present invention limits the range of V and Sc elements to 0.04-0.12wt.%. When the total amount of Mg and Si is set at 2.0-2.4wt.%, in order to further improve the strength and heat resistance of the alloy, trace amounts of Cu (0.20-0.30wt.%) and Mn (0.40-0.60wt.%) are added; in order to obtain fine grain structure and improve the heat resistance of the alloy during hot extrusion and welding, trace amounts of V and Sc (0.08-0.12wt.%) are added at the same time. When the total amount of Mg and Si is set at 2.4-3.0wt.%, as the Mg and Si content increases, the extrudability of the alloy decreases, and the extruded grain structure is prone to coarsening due to the increase in the driving force of hot extrusion dynamic recrystallization. In order to improve the extrudability of the alloy and obtain a fine extruded grain structure, the Cu element content is reduced to 0.10-0.20wt.%, and the V and Sc element contents are increased to 0.12-0.16wt.%.

[0018] In the present invention, different Mn and Fe element contents are designed according to different V and Sc element contents, and the Mn / Fe content ratio is controlled to be set within the range of 1.0-1.7, which is also the key point of the present invention. During the ingot homogenization process, the Mn element can promote the transformation of the coarse lamellar β-AlFeSi phase formed during the casting process into a fine, granular α-AlFeMnSi phase, thereby improving the strength and toughness of the alloy. When the Mn content is too high, the Mn element combines with the Fe, V, and Sc elements to form coarse intermetallic compounds, which reduces the plastic deformation ability of the alloy; at the same time, part of the V and Sc elements are consumed, which reduces the effect of inhibiting recrystallization and grain growth. Therefore, the Mn element content in the Al-Mg-Si alloy needs to be strictly controlled. Based on the fact that the alloy has both high strength and excellent crash resistance, the Mn element content in the present invention is set at 0.20-0.60wt.%. When the Mn content is constant, the excessively high Fe content makes it impossible for the β-AlFeSi phase to be fully transformed into the α-AlFeMnSi phase, and the adverse effects of the β-AlFeSi phase cannot be fully eliminated, thereby affecting the strength and toughness of the alloy. Therefore, the Fe content in the Al-Mg-Si alloy needs to be strictly controlled. In the present invention, the Mn / Fe content ratio is set at 1.0-1.7, and the corresponding Fe content is set at 0.12-0.60wt.%. When the total amount of Mg and Si is set to 2.0-2.4wt.%, it corresponds to lower V and Sc element contents (0.08-0.12wt.%). In order to further improve the strength and crash resistance of the alloy, the Mn element content is set to 0.40-0.60wt.%, and the Fe element content is set to 0.24-0.60wt.%; when the total amount of Mg and Si is set to 2.4-3.0wt.%, it corresponds to higher V and Sc element contents (0.12-0.16wt.%). In order to avoid the formation of coarse intermetallic compounds, the Mn element content is reduced to 0.20-0.30wt.%, and the Fe element content is set to 0.12-0.30wt.%.

[0019] In the present invention, different Ni element contents are designed according to different Mg, Si, Cu, V, and Sc element contents, which is also the key point of the present invention. Ni combines with Al to form fine Al3Ni hard particles, which can effectively hinder the movement of dislocations and atomic diffusion migration under high temperature conditions, thereby improving the heat resistance and high temperature strength of the material. However, excessive addition of Ni content will cause the fine Al3Ni particles in the alloy to be transformed into long needles, which sharply reduces the extrudability and toughness of the alloy. Based on obtaining excellent heat resistance and crushing performance, when the total amount of Mg and Si is set to 2.0-2.4wt.%, the Ni element content is set to 0.10-0.15wt.%; when the total amount of Mg and Si is set to 2.4-3.0wt.%, the Ni element content is set to 0.05-0.10wt.%.

[0020] In some embodiments of the present invention, the components of the aluminum alloy further include Cr, Zn and Ti.

[0021] In some embodiments of the present invention, the components of the aluminum alloy include, by weight, Mg: 0.9-1.5, Si: 0.9-1.5, Fe: 0.12-0.60, Cu: 0.1-0.30, Mn: 0.2-0.6, V: 0.04-0.12, Sc: 0.04-0.12 and Ni: 0.05-0.15, Cr0-0.03, Zn 0-0.1 and Ti 0-0.03, with the balance being aluminum.

[0022] The sum of the weight percentages of Mg and Si is 2.0-3.0;

[0023] The weight ratio of Mg to Si is 1.0-1.20;

[0024] According to two aspects of the present invention, a method for preparing an aluminum alloy is provided, comprising the following steps:

[0025] S1: melting an aluminum ingot, adding a master alloy of the aluminum alloy component, alloying, and refining to obtain an aluminum melt;

[0026] S2: purifying the aluminum melt after standing, and casting to obtain an aluminum alloy ingot;

[0027] S3: homogenizing the aluminum alloy ingot.

[0028] In some embodiments of the present invention, in step S1, the alloying temperature is 730-750°C.

[0029] In some embodiments of the present invention, in step S1, aluminum ingots with a purity ≥99.7%, magnesium ingots with a purity ≥99.95%, ALSi20, AlCu50, AlV3, AlSc2, AlNi10 intermediate alloys, and Mn75%, Fe75% additives are selected as raw materials.

[0030] In some embodiments of the present invention, in step S1, the refining step includes: spraying and refining the aluminum alloy liquid in the furnace with a sodium-free refining agent for 20-40 minutes.

[0031] In some embodiments of the present invention, in step S1, the refining further includes standing for 20-40 minutes after slagging.

[0032] In some embodiments of the present invention, in step S2, the purification step includes: passing the aluminum melt through a flow channel into a degassing box for online degassing treatment: the rotor rotation speed is 300-400 rpm, and the argon flow rate is 3-5 cubic meters / hour; the degassed solution passes through the flow channel into the filter box, and is filtered online through a 40-60ppi foam ceramic filter plate.

[0033] In some embodiments of the present invention, in step S2, the casting temperature is 710-730°C.

[0034] The aluminum ingot is heated and melted at 730-750°C, and then the corresponding magnesium ingot, intermediate alloy, Mn agent and Fe agent are added. The Al-Mg-Si alloy within the composition range of the present invention is very easy to solidify and crystallize to form coarse intermetallic compounds during the smelting and casting process, which reduces the extrudability of the ingot and also leads to reduced heat resistance, crushing performance and welding performance of the extruded product. Therefore, the smelting process in the present invention needs special control: low-content AlV3, AlSc2, AlNi10 intermediate alloys are used, and the smelting temperature is controlled at 730-750°C, and the casting temperature is controlled at 710-730°C.

[0035] In some embodiments of the present invention, in step S3, the homogenization step includes a first-stage homogenization process, a second-stage homogenization process, and a third-stage homogenization process.

[0036] In some embodiments of the present invention, the first stage homogenization step includes: heating to 450°C-480°C at a rate of 4-8°C / min and then keeping the temperature for 3-6 hours.

[0037] In some embodiments of the present invention, the second stage homogenization step includes: heating to 530-550°C at a rate of 2-4°C / min and then keeping the temperature for 5h-8h.

[0038] In some embodiments of the present invention, the third stage homogenization treatment step includes: heating to 560-580° C. at a rate of 1-3° C. / min and then keeping the temperature for 1-2 hours.

[0039] Under the above conditions, the needle-shaped Fe-containing phase is fully transformed into fine particles, while the growth of nano-scale second phase particles is avoided. Subsequently, it is cooled to 300°C at a cooling rate of 2-4°C / min and then quickly cooled to room temperature by water mist to reduce the solid solution concentration of Mg and Si elements in the ingot and improve the extrudability of the ingot. The ingot averaging process described in the present invention, on the one hand, greatly improves the strength and toughness of the alloy by eliminating the adverse effects of the Fe element and inhibiting the growth of nano-scale second phase particles (such as Al3V, Al3Sc, Al6Mn, etc.); on the other hand, it greatly improves the extrudability of the alloy by eliminating the segregation of alloy components in the ingot and reducing the solid solution concentration of Mg and Si elements.

[0040] According to three aspects of the present invention, an aluminum profile is provided, wherein the raw material for preparing the aluminum profile includes the aluminum alloy.

[0041] The Al-Mg-Si aluminum profile of the present invention optimizes the contents of Mg, Si, Cu, Mn, V, Sc and Ni elements, the Mg / Si weight ratio and the Mn / Fe weight ratio in the Al-Mg-Si alloy, so that when the strength of the alloy reaches above 340 MPa, it still has excellent welding performance, thermal stability, crash resistance and extrudability.

[0042] The preparation process of the present invention is simple and easy to implement. The extrudability of the aluminum alloy of the present invention is guaranteed by the optimized smelting and homogenization treatment process, so that thin-walled multi-cellular structures can be prepared in industrial production; the comprehensive performance of the thin-walled multi-cellular structure is guaranteed by the optimized extrusion process.

[0043] The production method of the present invention has low cost, and the performance of the prepared thin-walled multi-cellular structure profile is better than that of the prior art.

[0044] In some embodiments of the present invention, the method for preparing the aluminum profile comprises the following steps: hot extruding the aluminum alloy, quenching it, and then subjecting it to aging treatment.

[0045] In some embodiments of the present invention, the hot extrusion process comprises: heating the homogenized ingot to 500-520° C. at a heating rate of 60-80° C. / min and extruding the ingot at an extrusion rate of 5-8 m / min.

[0046] In some embodiments of the present invention, the extrusion further includes quenching.

[0047] In some embodiments of the present invention, the quenching conditions are: cooling to room temperature by water-cooling quenching, the corresponding quenching temperature is 530-560°C, and the cooling rate is ≥1000°C / min.

[0048] The production method of Al-Mg-Si alloy extrusion material of the present invention is mainly characterized by hot extrusion process. The hot extrusion process of the present invention is as follows: the ingot is rapidly heated to 500-520°C at a heating rate of 60-80°C / min by a permanent magnet furnace, and a thin-walled multi-cellular structure profile is prepared at an extrusion rate of 5-8m / min, and then cooled to room temperature by water-cooling quenching, and the corresponding quenching temperature is 530-560°C and the cooling rate is ≥1000°C / min. The above hot extrusion process ensures that the Mg and Si elements in the alloy are fully dissolved in the aluminum matrix on the one hand, and eliminates the grain boundary segregation and precipitation-free precipitation zone in the alloy on the other hand, improves the grain boundary bonding strength in the extruded material, and inhibits the growth of nano-scale second phase particles. The cooled profile is straightened online, and the straightening ratio needs to be controlled at 1.5%-2.5%, and then kept at an aging temperature of 200-220°C for 4-8H. Through the straightening process and aging heat treatment control, the purpose of eliminating the internal stress in the material is achieved, and the tendency of the material to crack during the crushing process is reduced.

[0049] In some embodiments of the present invention, the aging treatment parameters include: aging at 200-220° C. for 4-8 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a cross-sectional view of a thin-walled multicellular structure profile prepared in the embodiment;

[0051] Figure 2 This is a photo of a thin-walled multi-cellular structure profile that was crushed without cracking;

[0052] Figure 3 This is a photo of cracks appearing after the thin-walled multi-cellular structure profiles are crushed;

[0053] Figure 4 This is a photo of a thin-walled multi-cellular structure profile being crushed and broken. DETAILED DESCRIPTION

[0054] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0055] Among the raw materials of the present invention:

[0056] Aluminum ingot: Aluminum ingots with a grade of Al99.7 are used, and the mass percentage of Al in the aluminum ingot is more than 99.70%, which meets the standard GB / T 1196-2017 "Aluminum Ingots for Remelting";

[0057] Magnesium ingot: The magnesium ingot is Mg9990, the mass percentage of Mg in the magnesium ingot is above 99.9%, which meets the standard GB / T 3499-2003 "Original Magnesium Ingot";

[0058] Alloy additives: Si is added with AlSi10 master alloy, Cu is pure copper, V is AlV3 master alloy, Sc is AlSc2 master alloy, Ni is AlNi10 master alloy, Mn and Fe are 75% additives, Ti is added in the form of grain refiner, the quality of the master alloy conforms to GB / T 27677-2017 standard, and the refiner conforms to YS / T 447.1-2011 Alloy wire for grain refinement of aluminum and aluminum alloys Part 1: Refining gas: High-purity argon is used, and the purity, i.e., volume percentage, is ≥99.999%;

[0059] Melting online processing gas: high-purity argon gas is used, and the purity, i.e. the volume percentage, is ≥99.999%.

[0060] Example 1

[0061] This embodiment provides an aluminum alloy and a preparation method thereof. The composition of the aluminum alloy is shown in Table 1. The preparation method comprises the following steps:

[0062] S1: The aluminum ingots in the above raw materials are loaded into a smelting furnace and heated to melt at 730°C, and then the corresponding magnesium ingots, master alloys, Mn agents, and Fe agents are added, and the aluminum alloy liquid in the furnace is sprayed and refined with a sodium-free refining agent for 20 minutes, and the aluminum melt is allowed to stand for 20 minutes after slagging;

[0063] S2: The aluminum melt passes through the launder and enters the degassing box for online degassing treatment: the rotor rotation speed is 300 rpm and the argon flow rate is 3 cubic meters per hour; the degassed solution passes through the launder and enters the filter box, and is filtered online through a 40ppi high-temperature resistant ceramic filter plate, and the aluminum alloy liquid is semi-continuously cast into aluminum alloy ingots under the conditions of a casting temperature of 710°C, a casting speed of 70mm / min, and a cooling water flow rate of 2500ml / min;

[0064] S3: homogenizing the aluminum alloy ingot, the first stage: heating to 450°C at a speed of 4°C / min and then keeping the temperature for 3 hours, mainly to disperse and precipitate nano-scale Mn-containing phase particles; the second stage: heating to 530°C at a speed of 2°C / min and then keeping the temperature for 6 hours, mainly to eliminate the segregation of alloy components in the ingot; the third stage: finally heating to 560°C at a speed of 1°C / min and then keeping the temperature for 2 hours to obtain the aluminum alloy ingot;

[0065] S4: The ingot is rapidly heated to 500°C at a heating rate of 60°C / min in a permanent magnet furnace, and a thin-walled multi-cellular structure profile is prepared at an extrusion rate of 8m / min, such as Figure 1As shown, then, it is cooled to room temperature by water cooling quenching, the corresponding quenching temperature is 530℃, the cooling rate is ≥1000℃ / min, the cooled profile is straightened online, the straightening ratio needs to be controlled at 1.5%, and then kept at 200℃ aging temperature for 8h.

[0066] Embodiments 2 to 8

[0067] Examples 2 to 8 provide an aluminum alloy and a preparation method thereof. The composition of the aluminum alloy is shown in Table 1, and the preparation method is the same as that of Example 1.

[0068] Example 9

[0069] Example 9 provides an aluminum alloy and a preparation method thereof. The composition of the aluminum alloy is shown in Table 1. The preparation method comprises the following steps:

[0070] S1: The aluminum ingots in the above raw materials are loaded into a smelting furnace and heated to melt at 750°C, and then the corresponding magnesium ingots, master alloys, Mn agents, and Fe agents are added, and the aluminum alloy liquid in the furnace is sprayed and refined with a sodium-free refining agent for 20 minutes, and the aluminum melt is allowed to stand for 20 minutes after slagging;

[0071] S2: The aluminum melt passes through the launder and enters the degassing box for online degassing treatment: the rotor rotation speed is 300 rpm and the argon flow rate is 3 cubic meters per hour; the degassed solution passes through the launder and enters the filter box, and is filtered online through a 40ppi high-temperature resistant ceramic filter plate, and the aluminum alloy liquid is semi-continuously cast into aluminum alloy ingots under the conditions of a casting temperature of 730°C, a casting speed of 60mm / min, and a cooling water flow rate of 2500ml / min;

[0072] S3: homogenizing the aluminum alloy ingot, the first stage: heating to 460°C at a speed of 7°C / min and then keeping the temperature for 4 hours, mainly to disperse and precipitate nano-scale Mn-containing phase particles; the second stage: heating to 540°C at a speed of 3°C / min and then keeping the temperature for 8 hours, mainly to eliminate the segregation of alloy components in the ingot; the third stage: finally heating to 580°C at a speed of 3°C / min and keeping the temperature for 1 hour to obtain the aluminum alloy ingot;

[0073] S4: The ingot is rapidly heated to 500°C at a heating rate of 80°C / min in a permanent magnet furnace, and a thin-walled multi-cellular structure profile is prepared at an extrusion rate of 5m / min, such as Figure 1 As shown, then, it is cooled to room temperature by water cooling quenching, the corresponding quenching temperature is 540℃, the cooling rate is ≥1000℃ / min, the cooled profile is straightened online, the straightening ratio needs to be controlled at 2.2%, and then kept at 210℃ aging temperature for 4h.

[0074] Comparative Examples 1, 3, 5-11, 13

[0075] Comparative Examples 1, 3, 5-11, and 13 provide an aluminum alloy and a preparation method thereof. The composition of the aluminum alloy is shown in Table 1, and the preparation method is the same as that of Example 1.

[0076] Comparative Examples 2, 4, 12, 14

[0077] Comparative Examples 2, 4, 12, and 14 provide an aluminum alloy and a preparation method thereof. The composition of the aluminum alloy is shown in Table 1, and the preparation method is the same as that of Example 9.

[0078] Comparative Example 15

[0079] Comparative Example 15 provides an aluminum alloy and a preparation method thereof, which differs from Example 1 in that AlV5, AlSc15, and AlNi20 are used, the melting temperature is controlled at 710-730°C, the casting temperature is controlled at 690-710°C, and the other conditions are the same as Example 1.

[0080] Comparative Example 16

[0081] Comparative Example 15 provides an aluminum alloy and a preparation method thereof, which differs from Example 8 in that AlV5, AlSc15, and AlNi20 are used, the melting temperature is controlled at 710-730°C, the casting temperature is controlled at 690-710°C, and the other conditions are the same as Example 8.

[0082] Comparative Example 17

[0083] Comparative Example 17 provides an aluminum alloy and a preparation method thereof, which differs from Example 1 in that the homogenization temperature is 560°C and maintained for 12 hours, the alloy is cooled to 420°C with water mist and then air-cooled to room temperature, and the other conditions are the same as Example 1.

[0084] Comparative Example 18

[0085] Comparative Example 18 provides an aluminum alloy and a preparation method thereof, which differs from Example 8 in that the homogenization temperature is 560°C and maintained for 12 hours, the alloy is cooled to 420°C with water mist and then air-cooled to room temperature, and the other conditions are the same as Example 8.

[0086] Comparative Example 19

[0087] Comparative Example 19 provides an aluminum alloy and a preparation method thereof, which differs from Example 1 in that a natural gas heating furnace is used, the aluminum rod temperature is 500°C, the heating time is 6 hours, the extrusion speed is 6 m / min, and the other conditions are the same as Example 1.

[0088] Comparative Example 20

[0089] Comparative Example 20 provides an aluminum alloy and a preparation method thereof, which differs from Example 8 in that a natural gas heating furnace is used, the aluminum rod temperature is 500°C, the heating time is 6 hours, the extrusion speed is 6 m / min, and the other conditions are the same as Example 8.

[0090] Comparative Example 21

[0091] Comparative Example 21 provides an aluminum alloy and a preparation method thereof, the difference from Example 1 being the straightening process control range: 0.5%, and the other conditions are the same as Example 1.

[0092] Comparative Example 22

[0093] Comparative Example 22 provides an aluminum alloy and a preparation method thereof, the difference from Example 8 being the straightening process control range: 0.5%, and the other conditions are the same as Example 8.

[0094] Table 1. Weight percentage content of each component (wt.%)

[0095]

[0096]

[0097]

[0098] Table 2 Performance test results of aluminum alloy profiles obtained in the examples and comparative examples

[0099]

[0100]

[0101]

[0102] The mechanical properties test refers to "GB / T 228.12021 Tensile test of metallic materials Part 1: Room temperature test method". Tensile strength: the stress corresponding to the maximum force during the tensile test of the material; Yield strength: the stress corresponding to 0.2% plastic deformation during the tensile test of the material; Elongation after fracture: the ratio of the gauge length after the tensile test to the elongation before the tensile test; Extrusion discharge speed: the forward speed of the extruded profile per minute during the hot extrusion process; The crushing test refers to the "TL 1166xxx Aluminum Alloy Extrusion Profile Material Requirements" standard. The original length of the profile is 300mm. It is placed vertically between two parallel platens for axial crushing test. The compression stroke is 200mm and the compression speed is 100mm / min. The corresponding crushing cracking states include three forms: uncracked, cracked and fragmented. The corresponding photos are for reference Figure 2 , Figure 3 and Figure 4The heat resistance experiment refers to the "TL 116 6xxx Aluminum Alloy Extrusion Profile Material Requirements" standard to evaluate the rate of decrease in yield strength of the material after 1000 hours of insulation at 150°C; the welding strength test refers to the GB / T 2651-2023 "Welded Joint Tensile Test Method" standard to evaluate the rate of decrease in stress corresponding to the maximum force during the test compared to before welding.

[0103] It can be seen from Example 1 and Comparative Example 1 that when the sum of the weight percentages of Mg and Si elements is reduced from 2.0 to 1.8, the tensile strength of the alloy is reduced by 15 MPa due to the reduction of precipitation and solid solution strengthening effects.

[0104] It can be seen from Example 9 and Comparative Example 2 that: when the sum of the weight percentages of Mg and Si elements increases from 3.0 to 3.4, the extrudability of the alloy decreases, and the corresponding extrusion speed decreases from 5.0 m / min to 3.0 m / min, resulting in the profile not being cooled and quenched in time after extrusion. At the same time, the extruded grain structure coarsens due to the increase in the driving force of dynamic recrystallization of hot extrusion, resulting in a decrease in the tensile strength of the alloy by 50 MPa and cracking due to compression.

[0105] It can be seen from Example 5 and Comparative Example 3 that: when the Mg / Si weight ratio is increased from 1.0 to 1.7, the vacancy diffusion activation energy and the Zener-Hollomon parameter Z value of the alloy are increased, the corresponding hot extrusion deformation resistance is increased, and the extrudability is reduced. The corresponding extrusion speed is reduced from 8.0 m / min to 2.7 m / min, so that the profile cannot be cooled and quenched in time after extrusion. At the same time, the extruded grain structure is coarsened due to the increase in the hot extrusion dynamic recrystallization driving force, which leads to a 36 MPa decrease in the tensile strength of the alloy and crushing and fragmentation.

[0106] It can be seen from Example 9 and Comparative Example 4 that: when the Mg / Si weight ratio is reduced from 1.0 to 0.5, the excess Si element in the alloy increases. On the one hand, the content of precipitable Mg2Si is reduced, resulting in a 38MPa decrease in the tensile strength of the alloy; on the other hand, the precipitate phase is coarsened in the heat resistance experiment, which reduces the heat resistance of the alloy; at the same time, during the quenching and aging heat treatment process, the excess Si element is easily segregated at the grain boundary, reducing the grain boundary bonding strength, causing the alloy to collapse and crack.

[0107] It can be seen from Example 1 and Comparative Example 5 that when the Mn / Fe weight ratio is increased from 1.0 to 3.4, the alloy contains more Mn elements. On the one hand, it combines with Fe, V, and Sc elements to form coarse intermetallic compounds, which reduces the plastic deformation ability of the alloy; on the other hand, due to the consumption of more V and Sc elements, the number of nano-scale Al (V, Sc) second phase particles precipitated is reduced, which reduces the dispersion strengthening effect in the alloy and causes the coarsening of the extrusion and welding grain structure. Due to excessive addition of Mn elements, the tensile strength of the alloy is reduced by 27MPa, and cracking occurs due to compression. Figure 3 At the same time, the ratio of welding strength to parent material strength was reduced from 76.3% to 68.2%, and the profile of Example 1 was crushed without cracking. Figure 2 shown.

[0108] It can be seen from Example 6 and Comparative Example 6 that: when the Mn / Fe weight ratio is reduced from 1.0 to 0.6, the alloy contains more Fe elements, which makes it impossible for the β-AlFeSi phase to be fully transformed into the α-AlFeMnSi phase, and the adverse effects of the β-AlFeSi phase cannot be fully eliminated, resulting in the alloy being crushed and cracked.

[0109] It can be seen from Example 1 and Comparative Example 7 that when the weight percentage of V and Sc elements is increased from 0.09 to 0.20, and from Example 8 and Comparative Example 8 that when the weight percentage of V and Sc elements is increased from 0.16 to 0.2, the hot extrusion deformation resistance is increased during the hot extrusion process, so that the extrusionability of the alloy is reduced, and the corresponding extrusion speed is reduced from 8.0 m / min to 2.0 m / min, so that the profile cannot be cooled and quenched in time after extrusion, thereby resulting in a decrease in the tensile strength of the alloy and crushing and fragmentation.

[0110] It can be seen from Example 1 and Comparative Example 9 that when the weight percentage of V and Sc elements is reduced from 0.09 to 0.002, and from Example 8 and Comparative Example 10 that when the weight percentage of V and Sc elements is reduced to 0.002, the number of nano-scale Al (V, Sc) second phase particles is sharply reduced, the strengthening effect is reduced, and the extrusion and welding grain structure is coarsened, resulting in a decrease in alloy strength, welding performance, thermal stability and crushing performance.

[0111] It can be seen from Example 1 and Comparative Example 11 that when the weight percentage of the Cu element is reduced from 0.27 to 0.03, and from Example 9 and Comparative Example 12 that when the weight percentage of the Cu element is reduced from 0.12 to 0.03, the amount of Q phase (AlMgSiCu) formed by the combination of the Cu element with Mg and Si is reduced, so that the strength and thermal stability of the alloy are reduced.

[0112] It can be seen from Example 1 and Comparative Example 13 that: when the weight percentage of Ni element increases from 0.11 to 0.18, the fine Al3Ni particles in the alloy are transformed into long needles, which makes the extrusionability and toughness of the alloy decrease sharply. The corresponding extrusion speed is reduced from 8m / min to 2.5m / min, the tensile strength of the alloy is reduced by 19MPa, and it is crushed and broken.

[0113] It can be seen from Example 9 and Comparative Example 14 that when the weight percentage of Ni element is reduced from 0.10 to 0.001, the number of Al3Ni hard particles decreases and the heat resistance of the alloy decreases.

[0114] Through Example 1 and Comparative Example 15, Example 8 and Comparative Example 16: the use of high content of AlV5, AlSc15, AlNi20 intermediate alloys and inappropriate melting temperature (730-750°C) and casting temperature (710-730°C) can easily lead to solidification and crystallization of Al, Fe, V, and Sc elements to form coarse intermetallic compounds, which reduces the extrudability of the ingot, and also leads to reduced heat resistance, crushing performance and welding performance of the extruded product.

[0115] Through Example 1 and Comparative Example 17, Example 8 and Comparative Example 18, it can be known that: by adopting the conventional average process (keeping at 560°C for 12 hours, cooling to 420°C with water mist and then air cooling to room temperature), on the one hand, the adverse effects of the Fe element cannot be fully eliminated, and nano-scale second phase particles (such as Al3V, Al3Sc, Al6Mn, etc.) are prone to grow, which greatly reduces the strength and toughness of the alloy; on the other hand, the solid solution concentration of the alloy Mg and Si elements in the ingot is relatively high, which reduces the extrudability of the alloy.

[0116] It can be seen from Example 1 and Comparative Example 19, Example 8 and Comparative Example 20 that: when the conventional ingot heating process and extrusion speed (natural gas heating furnace, 500°C insulation for 6H, extrusion speed 6m / min) are adopted, the nano-scale Al(V, Sc) second phase particles in the alloy grow and their beneficial effects are weakened, resulting in a decrease in the alloy strength, heat resistance, crushing performance and welding performance.

[0117] It can be seen from Example 1 and Comparative Example 21, and Example 8 and Comparative Example 22 that: by lowering the straightening ratio, the residual stress generated by quenching in the extruded profile is not fully eliminated, which makes cracking easy to occur during the crushing process.

[0118] In the existing method, the strength of Al-Mg-Si alloy can be improved by increasing the content of Mg, Si, Mn and Cu elements. There are many problems when using the existing high-strength Al-Mg-Si alloy to hot extrude a thin-walled multicellular structure. The present invention optimizes the content of Mg, Si, Cu, Mn, V, Sc and Ni elements, the Mg / Si weight ratio and the Mn / Fe weight ratio in the high-strength Al-Mg-Si alloy, and provides a high-strength, heat-resistant, impact-resistant and weldable Al-Mg-Si thin-walled multicellular structure profile in combination with the preparation process.

[0119] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. An aluminum alloy, characterized in that: In terms of weight percentage, it includes the following components: Mg: 0.9-1.5, Si: 0.9-1.5, Fe: 0.12-0.60, Cu: 0.1-0.30, Mn: 0.2-0.6, V: 0.04-0.12, Sc: 0.04-0.12 and Ni: 0.05-0.15; The sum of the weight percentages of Mg and Si is 2.0-3.0; The weight ratio of Mg to Si is 1.0-1.

20.

2. The aluminum alloy according to claim 1, characterized in that When the sum of the weight percentages of Mg and Si is 2.0-2.4, the aluminum alloy includes the following components: Cu: 0.20-0.30, V+Sc: 0.08-0.12, Mn: 0.40-0.6, Fe: 0.24-0.60 and Ni: 0.10-0.

15.

3. The aluminum alloy according to claim 1, characterized in that When the sum of the weight percentages of Mg and Si is 2.4-3.0, the aluminum alloy includes the following components: Cu: 0.10-0.20, V+Sc: 0.12-0.16, Mn: 0.2-0.3, Fe: 0.12-0.30 and Ni: 0.05-0.

10.

4. The aluminum alloy according to claim 1, characterized in that The components of the aluminum alloy further include Cr, Zn and Ti.

5. The aluminum alloy according to claim 1, characterized in that The weight ratio of Mn to Fe is 1.0-1.

7.

6. A method for preparing an aluminum alloy as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: melting an aluminum ingot, adding a master alloy of the aluminum alloy component, alloying, and refining to obtain an aluminum melt; S2: purifying the aluminum melt after standing, and casting to obtain an aluminum alloy ingot; S3: homogenizing the aluminum alloy ingot.

7. The method for preparing the aluminum alloy according to claim 6, characterized in that: In step S3, the homogenization process includes a first-stage homogenization process, a second-stage homogenization process and a third-stage homogenization process; And / or, the first stage homogenization treatment step includes: heating to 450-480°C at a rate of 4-8°C / min and then keeping warm for 3-6 hours; and / or, the second stage homogenization treatment step includes: heating to 530-550°C at a rate of 2-4°C / min and then keeping warm for 5h-8h; and / or, the third stage homogenization treatment step includes: heating to 560-580°C at a rate of 1-3°C / min and then keeping warm for 1-2h.

8. An aluminum profile, characterized in that: The raw material for preparing the aluminum profile includes the aluminum alloy as claimed in any one of claims 1 to 5.

9. The method for preparing an aluminum profile according to claim 8, characterized in that: The method for preparing the aluminum profile comprises the following steps: hot extruding the aluminum alloy, quenching it and then subjecting it to aging treatment.

10. The method for preparing an aluminum profile according to claim 9, characterized in that: The hot extrusion process comprises: heating the homogenized ingot to 500-520° C. at a heating rate of 60-80° C. / min and extruding the ingot at an extrusion rate of 5-8 m / min.